STRUCTURE POWER AIRCRAFT FUSELAGE 5774 TRAINER - Pratama, Fandi Syafri (Vortex, 2021)
The analysis process using software aims to determine whether an object or material is suitable for use or not before carrying out the manufacturing process. To find out whether the material is strong or not when applied to the aircraft, an analysis is carried out using the ABAQUS CAE 6.14 software. This software will show the stress value that occurs in the sandwich composite structure when it receives the load experienced by the aircraft.